Pengaruh Kualitas, Presepsi Harga, Dan Citra Merek Terhadap Minat Beli Ulang Produk The Executive Di Kota Semarang Dengan Keputusan Pembelian Sebagai Variabel Intervening - Shakti, Niko Wildhan; Mahmud, Mahmud; Panjaitan, Roymon; Purusa, Nanda Adhi (Politeknik Negeri Ambon, 2024)
The fashion industry is currently very competitive. Most fashion brands provide necessities that are used in everyone's lives. The fashion in question is clothes from the executive. This research aims to examine the influence of quality, price perception, and brand image on the decision to repurchase executive products in Semarang City with the purchase decision being an intervening variable. The method used in this research is quantitative. The method for obtaining samples used a purposive sampling technique using 175 respondents using questionnaires via Google form. In the data analysis process, SMARTPLS is used. The results of data processing imply that brand image does not have a significant influence on repurchase interest in the executive products in Semarang, while price and product quality have a significant influence on purchasing decisions and repurchase interest in the executive brand in the city of Semarang. Keywords: Quality, Price Perception, Brand Image, Purchase Decision and Repurchase Intention